Treatment of Upper Lumbar Disc Herniation with a Transforaminal Endoscopic Technique - Wang, Zuowei; Jian, Fengzeng; Wu, Hao; Wang, Xingwen; Wang, Kai; Duan, Wanru; Liu, Zhenlei; Chen, Zan (Frontiers in Surgery, 2022)
Objective To investigate the clinical efficacy of percutaneous endoscopic transforaminal discectomy (PETD) in the treatment of upper lumbar disc herniation (LDH). Methods Twenty-two patients, 14 males and 8 females with ages ranging from 23 to 76 years, who had upper LDH and were treated with PETD from April 2015 to April 2020 in the Department of Neurosurgery of Xuanwu Hospital, were selected to evaluate the surgical efficacy by the visual analog scale (VAS) and Oswestry Disability Index (ODI). Results All patients underwent successful completion of PETD surgery. The operation time was 80.4 ± 18.0 min; intraoperative fluoroscopy was used 17.1 ± 8.7 times; and the hospital stay was 3.2 ± 0.6 days. The VAS scores were 7.9 ± 1.2, 2.3 ± 1.5, 2.2 ± 1.3, and 2.1 ± 1.0 before the operation, 1 day and 3 months after the operation, and during the last follow-up, respectively. The postoperative VAS score was significantly lower than that before the operation (P < 0.01). The ODI scores before and 3 months after the operation were 59.8 ± 16.8 and 15.3 ± 8.2, respectively; thus, the postoperative score was decreased (P < 0.01). Conclusion Upper lumbar discs have unique anatomical structures, and PETD is a safe and effective surgical method for the treatment of upper LDH.